(untitled) (Journal of Economics and Sustainability, 2024)
This study provides a comprehensive exploration of entrepreneurship education in Malaysia, focusing on institutional and government initiatives to stimulate innovation, economic growth, and job creation. Despite compulsory entrepreneurship subjects in public universities, a significant rise in graduate entrepreneurs remains elusive. The study assesses the state of entrepreneurship programs in Malaysian institutions and benchmarks them against Babson University in the United States. Content analysis and interviews scrutinize program outcomes and course offerings in Universiti Utara Malaysia and Universiti Malaysia Kelantan comparing them with Babson University. Secondary data, obtained through desktop reviews, illuminate Malaysia’s entrepreneurship education courses, assessed through university websites. Literature searches across databases and primary qualitative data offer in-depth insights, employing a mixed-methods approach to comprehensively address the research problem. Triangulation enhances data credibility, while qualitative and quantitative data from experienced entrepreneurs illuminate practical implications. Findings underscore the need for foundational entrepreneurship education, practical skills, and diverse courses. They emphasize a shift from a grade-centered to an experiential learning-focused approach, echoing calls for educational reform.